2020
DOI: 10.1088/1755-1315/420/1/012021
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of coral reef fish in the coastal water of Spelman Straits, Southeast Sulawesi

Abstract: Spelman Strait is one of the potential reef fisheries. This study aims to examine the potential of reef fisheries in the Spelman Strait. The data used in this study are primary data to determine the abundance of reef fish and the use of PaST (Paleontological Statistics) tools to assess diversity, Evenness, wealth, and dominance indices. The results showed that live coral cover from all observation stations was 37.71%. The abundance of reef fish has been under pressure, the diversity index still has good but so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…Another factor that causes differences in the number and type of fish is food availability and the time of observation [9]. Many factors can influence the number of fish found in the reef areas, primarily water temperature and current [10,[21][22][23], and interaction among fish groups of indicator fish, major fish, and target fish [24][25].…”
Section: Reef Fish Distributionmentioning
confidence: 99%
“…Another factor that causes differences in the number and type of fish is food availability and the time of observation [9]. Many factors can influence the number of fish found in the reef areas, primarily water temperature and current [10,[21][22][23], and interaction among fish groups of indicator fish, major fish, and target fish [24][25].…”
Section: Reef Fish Distributionmentioning
confidence: 99%
“…Trends in CPUE and fish size are heavily affected by non-environmentally friendly fishing practices, such as the use of explosives, resulting in fewer and smaller catches using the hand line by fishermen. Muis et al, (2019Muis et al, ( , 2020 confirmed that some fishermen still use explosives to capture reef fish in the coastal waters of the Spelman Strait. The fishing ground is far from the fish landing site (TPI) because the coral reef environment has been damaged due to destructive fishing that the community has carried out for a long time.…”
Section: Fish Resources Managementmentioning
confidence: 99%
“…Muis et al (2019) reported that the living coral cover in the coastal waters of Spelman Strait were moderate requirements (37.71%). The decline in live coral cover has been caused by destructive fishing, as shown during observation by several coral fragments (Muis et al, 2020). Therefore, these two sensitive characteristics need to be managed by carrying out restoration/transplantation of coral reef, especially in the main habitat of fish with high stocks and economic value, such as the Serranidae and Lutjanidae families.…”
Section: Figure 5 Habitat Environment and Ecosystem Factorsmentioning
confidence: 99%
See 2 more Smart Citations